Web-Based Language Learning for Enhancing Students’ Soft Skills in Mount Kenya University - Ongonda, Anashia; Muindi, Mary Nguvi (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
The application of an appropriate teaching methodology plays an important role in the acquisition of language skills. Soft skills such as oral and listening skills are all important for young adults who are about to enter the working world. However, soft skills are not well captured in the curriculum at the university level. Thus, employing Task-Based Language Teaching (TBLT) may hinder learners from noticing these important skills that are useful in real life. This study aims to demonstrate that the combination of TBLT and web-based language learning enhances student’s ability to acquire soft skills that are paramount in their real life. The following hypothesis guided the study: soft skills are enhanced through the use of a combination of task-based language teaching and web-based language learning. The experimental research design was used for the current study where a pre-test/post-test methodology was utilized. The target population for the current study was 300 third-year students studying English as a second language. Therefore, thirty students formed a sample size of the current study and were subjects of the experiment during one semester. The experiment consisted of exposing two groups fifteen each, randomly sampled, to a set of activities but using different methods, one of which was Computer Assisted Language Learning. Participant observation method was also used and was deemed important for the interpretation of the quantitative data. Data were analysed quantitatively. Thus, the results of the current study were derived from statistical analysis. The mean in the performance of the control group and the experimental group was significantly different. The findings of the study show that when learners are exposed to the web and visual aids, they become actively involved in the process of learning unlike in an aural environment. The study recommends the use of Computer Assisted Language Learning as a method of motivating and enhancing student’s development of soft skills. The application of an appropriate teaching methodology plays an important role in the acquisition of language skills. Soft skills such as oral and listening skills are all important for young adults who are about to enter the working world. However, soft skills are not well captured in the curriculum at the university level. Thus, employing Task-Based Language Teaching (TBLT) may hinder learners from noticing these important skills that are useful in real life. This study aims to demonstrate that the combination of TBLT and web-based language learning enhances student’s ability to acquire soft skills that are paramount in their real life. The following hypothesis guided the study: soft skills are enhanced through the use of a combination of task-based language teaching and web-based language learning. The experimental research design was used for the current study where a pre-test/post-test methodology was utilized. The target population for the current study was 300 third-year students studying English as a second language. Therefore, thirty students formed a sample size of the current study and were subjects of the experiment during one semester. The experiment consisted of exposing two groups fifteen each, randomly sampled, to a set of activities but using different methods, one of which was Computer Assisted Language Learning. Participant observation method was also used and was deemed important for the interpretation of the quantitative data. Data were analysed quantitatively. Thus, the results of the current study were derived from statistical analysis. The mean in the performance of the control group and the experimental group was significantly different. The findings of the study show that when learners are exposed to the web and visual aids, they become actively involved in the process of learning unlike in an aural environment. The study recommends the use of Computer Assisted Language Learning as a method of motivating and enhancing student’s development of soft skills.